Influence of change management on modern organizational efficiency - Ugo Chuks Okolie; Ndubuisi Jude Memeh (Jurnal Riset Ekonomi dan Bisnis, 2022)
In today's businesses, change is inevitable; hence it is crucial to research how change management and change variables impact organizational performance. This study's main objective is to examine change management and how it affects contemporary organizational effectiveness. A qualitative research method was used in this study, the primary source of information on the subject under consideration was previously published literature and contextual analysis was employed. The dynamics of change management and how it may be used to boost contemporary organizational effectiveness were examined in this study. The study also considered the function and actions of change-facilitating leaders. The study concludes that if certain conditions existed in organizations such as a strategic plan for implementing change, communication of change plans for employee buy-in, strategic change agents, implementation costs and maintenance of change tools, among others, change management would be successful. This study makes several recommendations, one of which is that organizations should convey the necessity of change because majority of people see change as disturbing and harmful. People tend to resist change if they don't have a feeling of urgency. Making existing conditions seem more needless than the desired changes is important to encourage an organization's acceptance of change.Perubahan tidak dapat dihindari; maka masih perlu dilakukan penelitian mengenai bagaimana manajemen perubahan dan variabel perubahan berdampak pada kinerja organisasi. Tujuan utama studi ini adalah untuk menguji manajemen perubahan dan bagaimana pengaruhnya terhadap efektivitas organisasi kontemporer. Penelitian kualitatif digunakan dengan sumber informasi utama adalah literatur yang diterbitkan sebelumnya dan analisis kontekstual. Dinamika manajemen perubahan diharapkan dapat meningkatkan efektivitas organisasi kontemporer diperiksa dalam penelitian ini. Studi ini mempertimbangkan fungsi dan tindakan pemimpin yang memfasilitasi perubahan. Diperoleh kesimpulan jika dalam organisasi terdapat rencana strategis untuk mengimplementasikan perubahan, komunikasi rencana perubahan untuk pembelian karyawan, agen perubahan strategis, biaya implementasi dan pemeliharaan alat perubahan, antara lain, manajemen perubahan akan berhasil. Kajian ini memberikan beberapa rekomendasi, salah satunya organisasi harus menyampaikan perlunya perubahan karena mayoritas orang melihat perubahan sebagai hal yang mengganggu dan merugikan. Orang cenderung menolak perubahan jika mereka tidak memiliki perasaan mendesak. Menciptakan kondisi tampak lebih tidak diperlukan daripada perubahan yang diinginkan adalah penting untuk mendorong penerimaan organisasi terhadap perubahan.